Teknik Evaluasi Non Tes di MI - Elan Elan; Supardi Supardi (Jurnal keilmuan dan Kependidikan dasar, 2013)
Measure activity, assess, and evaluate it is important in education. This is not independent because it is a cycle of activities required to determine the extent of educational achievement has been accomplished. For example in the evaluation of student lear-ning outcomes assessment, the measurement and assessment activities is the first step in the evaluation process. Activity mea-surements made are usually stated in various forms of tests and this is the most widely used. However, the test is not the only tool in the process of measurement, assessment, and evaluation of education because there are other techniques that technique non tes. Non-test technique is usually done by way of interviews, dis-tributing questionnaires, observations, performance, project work, a biography. In the evaluation of learning outcomes assess-ment, this technique is usually used to measure the affective and psychomotor domains, whereas the test technique used to mea-sure the cognitive domain